2018
DOI: 10.2134/cftm2017.11.0085
|View full text |Cite
|
Sign up to set email alerts
|

Boron Fertilization of Irrigated Alfalfa in Montana

Abstract: Core Ideas Boron (B) application increased petiole B in irrigated alfalfa but did not impact yield and quality. Low initial soil B is not a reliable measure of the need to amend with B using foliar application of irrigated alfalfa in Montana. Diagnosing signs of B deficiency coupled with in‐season petiole B analysis may be of better value to the producers. A boron (B) deficient soil may negatively impact irrigated alfalfa (Medicago sativa L.) plant tissue sufficiency, thereby compromising yield and quality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Overall, the effect of B on total yield was nonsignificant in northwestern Montana, similar to reported findings in literature (Grant and Miller, 1998; Pecinovsky and Lang, 2012; Razmjoo and Henderlong, 1997; Sapkota et al, 2017, 2018). Razmjoo and Henderlong (1997) found that application of B up to 2 kg ha −1 did not affect alfalfa yield in Columbus, Ohio on a Crosby silty clay loam soil.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, the effect of B on total yield was nonsignificant in northwestern Montana, similar to reported findings in literature (Grant and Miller, 1998; Pecinovsky and Lang, 2012; Razmjoo and Henderlong, 1997; Sapkota et al, 2017, 2018). Razmjoo and Henderlong (1997) found that application of B up to 2 kg ha −1 did not affect alfalfa yield in Columbus, Ohio on a Crosby silty clay loam soil.…”
Section: Discussionsupporting
confidence: 89%
“…Razmjoo and Henderlong (1997) found that application of B up to 2 kg ha −1 did not affect alfalfa yield in Columbus, Ohio on a Crosby silty clay loam soil. Similary, Grant and Miller (1998) and Sapkota et al (2018) reported no increases in alfalfa yield with increased B rate applications. Our recent study documented that the B uptake of alfalfa (i.e., 0.06–0.08 kg B Mg −1 production in reference to the control treatment, Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The performance of numerous agricultural plants was improved using boron fertilizers, most importantly in terms of yield, but also in terms of quality and certain physiological parameters, e.g., water management and chlorophyll content. Given the narrow range between deficiency and toxicity, the dosage of the added boron should be carefully adjusted for each application [164][165][166][167][168][169][170][171].…”
Section: Alleviation Of the Effects Of Boron Deficiency And Toxicitymentioning
confidence: 99%
“…Cotton grown in greenhouse experiments responded with increased dry matter yield, taller plants, and more reproductive structures per plant as concentration of B in the nutrient solution increased (Bogiani et al, 2014). However, when alfalfa grown in low‐B soils in Montana was fertilized with liquid B fertilizer, there was only a yield response in one cutting out of eight measured over two years and two sites, and quality of the alfalfa hay was not impacted by the applications (Sapkota et al, 2018). Toxicity can happen at low concentrations of B, coffee plants grown in a nutrient solution displayed impacts of B toxicity at a concentration of 0.50 ppm, with death at of the plants at 2.0 ppm B in the solution (Vasco et al, 2018).…”
Section: Rate and Placementmentioning
confidence: 99%